1970
DOI: 10.5424/sjar/20110902-166-10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on morphological and yield traits in cotton (Gossypium hirsutum L.)

Abstract: The nature and magnitude of genetic effects on morpho-yield traits were studied in a 6 × 6 F 1 and F 2 diallel cross in upland cotton. An additive-dominance model was adequate for most of the traits except plant height and seed cotton yield, where the model was partially adequate. Genetic parameters were estimated following Hayman's and Mather's model. Additive effects controlled lint percentage and monopodia in both generations, and plant height and sympodia in F 2 . Non-additive inheritance with over-dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
10
16
0
Order By: Relevance
“…The value of H 2 /4H 1 was less than 0.25, which depicted unequal distribution of genes for the trait among the parents for all the traits under normal and hypoxic conditions. Negative F value was observed for staple length under normal and for seed cotton yield under hypoxia signified the unimportant role of dominant genes which are in conformity to the findings of Khan and Hassan (2011), which reported negative F value for lint percentage and seed cotton yield in the F 1 generation, same researchers reported positive values for these traits while studying F 2 generation. The dominance additive ratio represents the degree of dominance.…”
Section: Genetic Componentssupporting
confidence: 75%
See 1 more Smart Citation
“…The value of H 2 /4H 1 was less than 0.25, which depicted unequal distribution of genes for the trait among the parents for all the traits under normal and hypoxic conditions. Negative F value was observed for staple length under normal and for seed cotton yield under hypoxia signified the unimportant role of dominant genes which are in conformity to the findings of Khan and Hassan (2011), which reported negative F value for lint percentage and seed cotton yield in the F 1 generation, same researchers reported positive values for these traits while studying F 2 generation. The dominance additive ratio represents the degree of dominance.…”
Section: Genetic Componentssupporting
confidence: 75%
“…The estimation of genetic components of variation revealed that value of additive component (D) was positive and significant found more than the values of dominance components (H 1 ) and (H 2 ) indicating the important role of additive and non-additive effects in controlling all the characters studied. Khan and Hassan (2011) reported additive effects for ginning out-turn percentage and non-additive effects for seed cotton yield. Moreover, Shakeel et al (2011) also reported about the contribution of additive effects in F 1 generation and non-additive effects in F 2 generation for seed cotton yield.…”
Section: Genetic Componentsmentioning
confidence: 99%
“…Raza et al (2013) evaluated five cultivars and detected additive effects to plant height, lint yield, lint percentage and boll weight. Khan and Hassan (2011) estimated the GCA and SCA in a diallel scheme involving 12 cotton cultivars and found differences in all hybrid combinations to lint yield, boll weight and boll numbers, with more genetic variances to SCA than to GCA indicating predominance of non-additive gene.…”
Section: Introductionmentioning
confidence: 99%
“…It contributes to the oil and seed sector as well as fiber industries [1]. Pakistan's economy totally relies upon cotton production directly or indirectly [1] [2]. Among the four cultivated species of cotton, Gossypium arboreum also called "true cotton", is a specie native to the Indian subcontinent and presently used in introgressive breeding as a donor species for improving resistance to insect pests and disease especially CLCuD in upland cotton [3] [4].…”
Section: Introductionmentioning
confidence: 99%